Estudo sobre a ocorrência e caracterização das Partículas de Exopolímeros Transparentes (TEP) no reservatório de Barra Bonita e sua colonização por bactérias - Fatibello, Silvia Helena Saboya Arruda (2005)
TEP (Transparent Exopolymer Particles) have a great importance in the microbiological processes, in the carbon cycle and in food chain dynamics of the aquatic ecosystems. These particles are composed by a gel matrix formed mainly by acid polysaccharides dissolved and/or colloidal those are released by phytoplankton microorganisms. TEP are abundant in the oceans and in fresh waters and they have a dimension that varies from some micra to millimeters. This current work has the main objective of quantify and study the distribution per range of the TEP present in Barra Bonita reservoir water column in the Tietê River in the period between September of 2002 and January of 2004. Further the bacteria attached to TEP were quantified as well as preliminary protocols were established to the biological molecular analysis (DNA extraction, PCR e DGGE) of the bacteria attached to the TEP. During this study, the TEP concentration (> 1 µm), determined by a spectrophotometric method developed in this thesis, varied from 0.02 to 3.10 equiv. GX µg mL-1 and by light microscopy from 5.4 x 103 to 1.6 x 105 particles mL-1. Although, during the study period, the average concentrations did not suffer significant variations because of the unstable and dynamic system with constant changes of the Barra Bonita reservoir nature. The abundance of TEP size decreased with the increase of the particles diameter show by the equation N = kdp -β used in studies of this nature. In this equation k is related to particles concentration and β is to particles distribution per class size. In this work the k value varied from 2.40 x 104 to 3.86 x 10 6 particles mL-1 and β value from 0.2 to 2.5, indicating a predominance of particles of smaller size in the reservoir. Regarding bacteria attached to TEP, they were found on the surface and in the interior of the particles in average concentrations varying from 9 to 45 bacteria (TEP)-1, showing that not all TEP were colonized by bacteria. The number of bacteria attached to TEP can not be related to the particle surface or volume. Considering the total of bacteria numbered by fluorescence microscopy, the percentage of bacteria attached to TEP varied from 6.9 to 80.3%. The adequation of protocols to the extraction and amplification of the DNAr 16S of the bacteria attached to TEP from the water samples were performed with success and the use of PCR/DGGE techniques in these samples showed high diversity of bacteria community attached to TEP.